Zum Vorkommen der Sepsidae in unterschiedlichen Rasenökosystemen Thüringens (Diptera, Sepsidae). - Bährmann, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1993)
1. Sepsidae were investigated in different naturelike and polluted lawn biotopes of Thuringia including niche data in space and time. 20 species have been caught. 16 species were found in more or less moist and 12 in half dry and dry grassland ecosystems. - 2. The most numerous species of the investigated ecosystems are Sepsis fulgens, S. cynipsea, S. orthocnemis, S. violacea and Themira annulipes. - 3. Niche overlap of the highest-ranking species in the Leutra valley near Jena/Thuringia has shown that there are two ecological groups of sepsids reflecting probably differences in the niche variables such as mesoclimatic conditions. The moisture of the ground could be a most important one among them. - 4. Furthermore the results of the ecological studies give some evidence of seasonal migrations in the more common Sepsis species, for instance S. fulgens, S. orthocnemis and S. cynipsea.